Positron Emission Tomography with [18F]FLT Revealed Sevoflurane-Induced Inhibition of Neural Progenitor Cell Expansion in vivo - Liu, Shuliang; Paule, Merle G.; Zhang, Xuan; Newport, Glenn D.; Patterson, Tucker A.; Apana, Scott M.; Berridge, Marc S.; Maisha, Mackean P.; Slikker, William; Wang, Cheng (Frontiers in Neurology, 2014)
Neural progenitor cell expansion is critical for normal brain development and an appropriate response to injury. During the brain growth spurt, exposures to general anesthetics which either block the N-methyl D-aspartate receptor or enhance the γ-aminobutyric acid receptor type A can disturb neuronal transduction. This effect can be detrimental to brain development. Until now, the effects of anesthetic exposure on neural progenitor cell expansion in vivo had seldom been reported. Here, minimally invasive micro positron emission tomography (microPET) coupled with 3'-deoxy-3' [18F] fluoro-L-thymidine ([18F]FLT) was utilized to assess the effects of sevoflurane exposure on neural progenitor cell proliferation. FLT, a thymidine analogue, is taken up by proliferating cells and phosphorylated in the cytoplasm, leading to its intracellular trapping. Intracellular retention of [18F]FLT, thus, represents an observable in vivo marker of cell proliferation. Here, postnatal day (PND) 7 rats (n = 11/ group) were exposed to 2.5% sevoflurane or room air for 9 hr. For up to two weeks following the exposure, standard uptake values (SUVs) for [18F]-FLT in the hippocampal formation were significantly attenuated in the sevoflurane-exposed rats (p <0.0001), suggesting decreased uptake and retention of [18F]FLT (decreased proliferation) in these regions. Four weeks following exposure, SUVs for [18F]FLT were comparable in the sevoflurane-exposed rats and in controls. Co-administration of 7-nitroindazole (7-NI, 30 mg/kg, n = 5), a selective inhibitor of neuronal nitric oxide synthase, significantly attenuated the SUVs for [18F]FLT in both the air-exposed (p = 0.00006) and sevoflurane-exposed rats (p = 0.0427) in the first week following the exposure. These findings suggested that microPET in couple with [18F]FLT as cell proliferation marker could be used as a non-invasive modality to monitor the sevoflurane-induced inhibition of neural progenitor cell proliferation in vivo.